Microtubule‐Targeting 7‐Deazahypoxanthines Derived from Marine Alkaloid Rigidins: Exploration of the N3 and N9 Positions and Interaction with Multidrug‐Resistance Proteins. (25th January 2019) - Dasari, Ramesh; Błauż, Andrzej; Medellin, Derek C.; Kassim, Roaa M.; Viera, Carlos; Santarosa, Maximo; van der Westhuyzen, Alet E.; van Otterlo, Willem A. L.; Olivas, Taryn; Yildiz, Tugba; Betancourt, Tania; Shuster, Charles B.; et al.
Abstract: Our laboratories have been investigating synthetic analogues of marine alkaloid rigidins that possess promising anticancer activities. These analogues, based on the 7‐deazahypoxanthine skeleton, are available in one‐ or two‐step synthetic sequences and exert cytotoxicity by disrupting microtubule dynamics in cancer cells. In the present work we extended the available structure–activity relationship (SAR) data to N3‐ and N9‐substituted derivatives. Although N3 substitution results in loss of activity, the N9‐substituted compounds retain nanomolar antiproliferative activities and the anti‐tubulin mode of action of the original unsubstituted compounds. Furthermore, our results also demonstrate that multidrug‐resistance (MDR) proteins do not confer resistance to both N9‐unsubstituted and ‐substituted compounds. It was found that sublines overexpressing ABCG2, ABCC1, and ABCB1 proteins are as responsive to the rigidin analogues as their parental cell lines. Thus, the study reported herein provides further impetus to investigate the rigidin‐inspired 7‐deazahypoxanthines as promising anticancer agents. Abstract : Expanding marine bounty : Analogues of marine alkaloid rigidins, based on the 7‐deazahypoxanthine skeleton, are available in one‐ or two‐step synthetic sequences and exert cytotoxicity by disrupting microtubule dynamics in cancer cells. In this work we extended the available SAR data to N3‐ and N9‐substituted derivatives. Furthermore, multidrug‐resistance proteins do not confer resistance to both N9‐unsubstituted and ‐substituted compounds. These results provide further impetus to investigate the rigidin‐inspired 7‐deazahypoxanthines as promising anticancer agents.